Tradition in transformation: the classical curriculum in the colonial and early national American college. (17th January 2020) - Fisher, Gary F
Abstract: Narratives of decline dominate histories of classical education. Changes or developments in the way classics have been taught are commonly understood in terms of the supposedly inexorable decline of classical learning. The American colleges at the end of the eighteenth century are subject to the same interpretation. After the Revolution, the colleges and their classics-oriented curriculum were subject to new pressures to reform the education they offered to better reflect the values of the new nation. These calls for reform are commonly understood as attacks on the classics that sought to diminish their role in, or even remove them from, the college curriculum. This essay will subject materials such as entrance requirements, curricula, and reformist literature to a critical re-reading. Rather than examining the extent to which the position of the classics diminished relative to other subjects during this period, it will show how the content of the classical curriculum was reformed and refined to better realize its pedagogical potential and ensure its relevance to the changing needs of students.